Implementasi Model Pembelajaran Berbasis Blended Learning Untuk Meningkatkan Kemampuan Keterampilan Berpikir Kritis dan Hasil Belajar Siswa SD - Yunita Anggraeni Sutanti; Suryanti Suryanti; Zainal Arifin Imam Supardi (Cetta: Jurnal Ilmu Pendidikan, 2021)
This study aims to apply the blended learning model to improve critical thinking skills and learning outcomes in elementary school students. This research is a research with a quasi-experimental approach (Quasi Experimental). The design used is the Pretest-Posttest Non Equivalent Control Group Design. This research was conducted at SDN Jajartunggal III/452 Surabaya. This study focuses on Class VA and VB. So that the object of development research in this study is the implementation of the blended learning model to improve students' critical thinking skills and learning outcomes. The subjects of this study were 15 students in class VA and 16 students in VB. And the research was conducted for 1 week. In the implementation of the test, the science representation ability test was carried out in class V A and V B. The test subject for the science representation ability in the trial class was equivalent to the science representation ability of the research subject. From the results of the analysis, it was found that the average result of the pretest of critical thinking skills in grade 5 A students was 64.33, while the average post-test results of critical thinking skills in grade 5 B students was 86.25.